1991
DOI: 10.1038/bjc.1991.347
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer and ethnic group in Britain: a United Kingdom children's Cancer Study Group (UKCCSG) study

Abstract: Summary We present here the results of the largest study of childhood cancer and ethnic group in Britain, based on 7,658 children treated at paediatric oncology centres throughout the country. Incidence rates could not be calculated and so relative frequencies were analysed by the log-linear modelling method of Kaldor et al. (1990) with allowance made for regional variations in the ages and diagnostic groups of the children included in the study. Children of Asian (Indian sub-continent) Childhood neoplasms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 20 publications
5
41
0
Order By: Relevance
“…The distribution of the super profile categories in the two groups revealed that 73% of the Asian children were in the lowest three socioeconomic groups (VIII-X), compared with 26% of non-Asian children (P<0.0001, chi-square). Distribution of cancers by diagnostic groups (Birch and Marsden, 1987) in the Asian and non-Asian groups are given in Table II (Senior and Bhopal, 1994 (Stiller et al, 1991;Powell et al, 1994) The measure is also available for everyone with a recorded address. A disadvantage of this study is that, because Asian families are often concentrated in inner city areas, they will tend to be uniformly categorised as of low socioeconomic status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the super profile categories in the two groups revealed that 73% of the Asian children were in the lowest three socioeconomic groups (VIII-X), compared with 26% of non-Asian children (P<0.0001, chi-square). Distribution of cancers by diagnostic groups (Birch and Marsden, 1987) in the Asian and non-Asian groups are given in Table II (Senior and Bhopal, 1994 (Stiller et al, 1991;Powell et al, 1994) The measure is also available for everyone with a recorded address. A disadvantage of this study is that, because Asian families are often concentrated in inner city areas, they will tend to be uniformly categorised as of low socioeconomic status.…”
Section: Resultsmentioning
confidence: 99%
“…The United Kingdom Children's Cancer Study Group (UKCCSG) has examined the pattern of paediatric cancers and estimated the risk in different ethnic groups. A significant excess of Hodgkin's disease (HD) was observed among Asian children compared with Caucasians (estimated relative risk 2.09) (Stiller et al, 1991). Comparison of the age-standardised incidence rates of paediatric cancer in ethnic groups in the West Midlands has shown a significantly higher annual incidence of all cancers in Asian children (Powell et al, 1994).…”
mentioning
confidence: 99%
“…Analysis of a much larger series of HD cases by Gulley et al (1994) also showed an association with Hispanic ethnicity (P < 0.001). Several UK studies have shown that Asian children have a higher rate of HD, with an estimated relative risk of 2.09 (Stiller et al, 1991;Muir et al, 1992;Varghese et al, 1996), but data on the frequency of EBV positivity in these tumours is not available. We were not able to determine ethnic or racial origin in our group of patients and the possibility that these factors may confound any association between EBV positivity in HD and material deprivation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Wilms tumor accounts for 8% of childhood cancers and occurs in 1 in 10 000 Caucasian children, though its incidence in East-Asian populations is half of that. (2) In Hawaii and Britain, the incidence of WT in people of Asian descent is about half to two-thirds of that in Caucasians, (3,4) suggesting that environmental factors play little part in the lower incidence.IGF2 is an imprinting gene expressed from the paternally inherited allele, and encodes a fetal polypeptide growth factor. Loss of imprinting (LOI) of IGF2 has been reported in various tumors, including pediatric tumors.…”
mentioning
confidence: 99%